The Utilization of Quarterly Learning Plan Towards Teachers’ Proficiency Under the Matatag Curriculum - Jasminie Francisco; Allen Cris Montillano (Edu Berkah Khatulistiwa, 2026)
This study aims to investigate the relationship between the utilization of the quarterly learning plan and teachers’ proficiency under the MATATAG Curriculum. Guided by goal-setting theory, which emphasizes structured planning, the research highlights how a quarterly learning plan enables educators to establish clear objectives for their professional development. Conducted at Maranatha Christian Academy of Cabuyao and Sta. Rosa, the study involved 38 teachers from various levels of the MATATAG Curriculum, specifically kindergarten, Grade 4, and Grade 7. Findings indicate a significant correlation between the functionality of utilization of the quarterly learning plan and teachers' proficiency levels. Notably, the results show that the quarterly learning plan's effectiveness is not influenced by diverse teacher profile variables, including age, educational attainment, and years of teaching experience. This suggests it serves as a universal framework that supports all educators. Additionally, the study reveals that teachers exhibit high competency in managing their workload while aligning with curriculum and assessment standards. Consistent utilization of the quarterly learning plan enhances teachers' proficiency in achieving their objectives, boosting motivation, and facilitating constructive feedback. This process fosters ongoing professional growth and promotes accountability and commitment to their roles. Ultimately, this research highlights the importance of structured planning in education, underscoring its vital role in enhancing teacher effectiveness and improving student learning outcomes within the MATATAG Curriculum framework.